Pediatric Traumatic Brain Injury; Experience in Tertiary Care Hospitals of KPK, A Multi- Center Study - Muhammad Idris Khan, Akram Ullah, Naeem Ul Haq, Main Ifthakar Ul Haq, Ramzan Hussain, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The present study examined the epidemiology, clinical features, and outcome of pediatric traumatic brain injuries (TBI) in tertiary care hospitals in Khyber Pakhtunkhwa (KPK) . Duration and Place of the Study: Duration of study was From February 2020 to February 2022.It was conducted in Neurosurgery Department, Khyber teaching hospital MTI, and Hayatabad medical complex Peshawar. Material and Methods: A total of Six hundred and forty-three pediatric patients, ages 01 to 11years, who had suffered traumatic brain injury were included in the study. All children were first seen at an emergency room, where they had a series of diagnostic tests and a physical examination. All necessary radiological studies were carried out under the watchful eye of the senior consultant neurosurgeon. In addition to demographic information, the pattern, treatment, and outcome of children with head injury were also recorded. Results: Among the 643 kids examined, 411 (or 65%) were boys, and 232 (or 35%) were girls. At presentation, the average age was 4.062 years. Among the children surveyed, 525 (82%) lived in an urban setting, while the remaining 117 (18%) lived in a rural region. Three hundred and seventy-eight (60%) of the children suffered a head injury secondary to fall, whereas just 207 (33%) had been involved in automobile accidents. 58% (374) had mild head injury and 185 29% had moderate head injuries, 84 (13%) had severe head injury. 12% (74) of patients underwent craniotomy for extra-dural hematoma. 46 (7.1%) of the children had depressed skull fracture which was surgically treated. 23 (3.5%) patient had acute sub-dural hematoma for which craniotomy was done. Rest of the 27(4.1%) children had traumatic sub-arachnoid hemorrhage and intracerebral bleed which were treated. Out of the total 76(11.6%) children did not recover and died, most of them presented with severe head injuries Conclusion: Most common cause for head injury in our setup was fall from height which was followed by motor vehicle accidents. Over half of the children presented mild to moderate head injuries. Over half were treated conservatively with good outcome. We had mortality of 11.6% with most having severe head injuries. Keywords: Mortality, Brain Injury, fall, Car Accidents, depressed skull fracture, extra-dural hematoma, acute sub-dural hematoma.